2015
DOI: 10.1002/2015wr017677
|View full text |Cite
|
Sign up to set email alerts
|

A framework of change‐point detection for multivariate hydrological series

Abstract: Under changing environments, not only univariate but also multivariate hydrological series might become nonstationary. Nonstationarity, in forms of change‐point or trend, has been widely studied for univariate hydrological series, while it attracts attention only recently for multivariate hydrological series. For multivariate series, two types of change‐point need to be distinguished, i.e., change‐point in marginal distributions and change‐point in the dependence structure among individual variables. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 75 publications
(157 reference statements)
2
45
0
Order By: Relevance
“…There are several methods on change‐point detection (e.g., Ivancic & Shaw, ; Xiong, Jiang, Xu, Yu, & Guo, ). Ivancic and Shaw () detected multiple change points in annual streamflow using all the U.S. Geological Survey flow gauges and attributed the cause of the abrupt changes in streamflow to natural variability in the climate signal.…”
Section: Methodsmentioning
confidence: 99%
“…There are several methods on change‐point detection (e.g., Ivancic & Shaw, ; Xiong, Jiang, Xu, Yu, & Guo, ). Ivancic and Shaw () detected multiple change points in annual streamflow using all the U.S. Geological Survey flow gauges and attributed the cause of the abrupt changes in streamflow to natural variability in the climate signal.…”
Section: Methodsmentioning
confidence: 99%
“…Vine copula, also known as pair‐copula construction, provides a solution for constructing multidimensional copula without requiring a conditional independence assumption (Aas et al, ). A few recent studies have demonstrated the applicability of vine copula to hydrology (e.g., Bevacqua et al, ; Xiong et al, ). These studies show the flexibility of vine copula in reproducing a wide range of dependence between multivariate variables, including heterogeneous dependence that could exist among different pairs (also see Liu et al, ; Vernieuwe et al, ; Xiong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…where cðÁÞ, f P ðÁÞ, f Ep ðÁÞ, f T ðÁÞ, and f k ðÁÞ denote the density functions of CðÁÞ, F P ðÁÞ, F Ep ðÁÞ, F T ðÁÞ, and F k ðÁÞ, respectively. It should be noted that the dependence structure of (P t ,Ep t ,T t ,k t ) could be nonstationary [Bender et al, 2014;Jiang et al, 2015a;Xiong et al, 2015], but in this study we prefer to assume a stationary dependence structure, that is, h c is constant for the whole observation period.…”
Section: Construction Of Multivariate Dependence Structure Using the mentioning
confidence: 99%